If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + 5x = 7x + -12 Reorder the terms: 12 + 5x = -12 + 7x Solving 12 + 5x = -12 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 12 + 5x + -7x = -12 + 7x + -7x Combine like terms: 5x + -7x = -2x 12 + -2x = -12 + 7x + -7x Combine like terms: 7x + -7x = 0 12 + -2x = -12 + 0 12 + -2x = -12 Add '-12' to each side of the equation. 12 + -12 + -2x = -12 + -12 Combine like terms: 12 + -12 = 0 0 + -2x = -12 + -12 -2x = -12 + -12 Combine like terms: -12 + -12 = -24 -2x = -24 Divide each side by '-2'. x = 12 Simplifying x = 12
| 7x+2=2(7x+2)+8 | | 75-what+10=60 | | 3(-1+2r)+9= | | 3r-2=22 | | -3(3p+2)-2(5-8p)=3(5+2p) | | 2(x-1)(x+5)=2-x(2x+16) | | Y=-6x-y | | (2f-3)f=18 | | 9d+4=94 | | 4t-11=29 | | p-3/7=6 | | x^2-16+(x+4)(x+1)=0 | | 2v-3=0 | | 10m+1=13 | | 6e=2(e+6)-(5-4e) | | x/12=3/8 | | X^2=-3-4x | | 180+.25x=320 | | .45(6)+.05x=.15(36+x) | | -2a-(1+6a)=-9-4a | | 2v^2+v-15=0 | | 2.5h-15=4*h | | (2i)*(3i)=x | | 5p(-6)=150 | | -6x^2+4x-9=0 | | (2i)*(3i)= | | 3x^2+15x-6=9 | | 26+6x=9x-8 | | 55-what+41=62 | | 6x-5(5-x)=52 | | 3x-13x-8x-4x=14 | | 3/23x4 |